Neutral and charged excitons in tungsten dichalcogenides monolayer. (2016) - Hichri, A.; Jaziri, S.
Monolayer transition metal dichalcogenides (TMDs) represent an alternative group of two dimensional (2D) layered materials that differ from the semimetallic character of graphene. They have aroused great attention owing to their peculiar physical properties, in particular the strong electron-hole interaction. Largely motivated by enhancement of the binding energies of exciton and trion in TMDs, we present a theoretical model to describe the formation of trion in monolayer WS2 and WSe2, obtained by exfoliating n-type bulk crystals. We show that the binding energies of excitonic states deviate strongly from the standard 2D Wannier Mott model owing to the correlations with the surrounding dielectric environment. Therefore, using a non-local dielectric screening potential, exciton and trion energies are shown to be in excellent agreement with photoluminescence (PL) measurements. According to the mass action law, we calculate the dependence of the intensity of neutral and charged excitons on temperature, pumping and injection electron.